Stable biofilms of Rhodococcus erythropolis T902.1 in draining pavement structures for runoff water decontamination. (August 2016) - Masy, Thibaut; Bertrand, Christelle; Xavier, Paul-Marie; Vreuls, Christelle; Wilmot, Anne; Cludts, Marc; Renard, Philippe; Mawet, Pascal; Smets, Sylvie; Dethy, Bernard; Thonart, Philippe; Jacques, Philippe; et al.
Abstract: Permeable Pavement Systems (PPS) are sustainable devices designed to collect, store and treat urban stormwater before its release into the ground. However, this system must sufficiently retain pollutants brought by water runoff in order to comply with the current legislation. This study aims at evaluating the implementation in PPS of a hydrocarbonoclastic bacterium, Rhodococcus erythropolis T902.1, in terms of resilience and improvement of the degrading capacity. First results revealed that this strain could durably colonize the different gravels used in the construction of PPS. A 15-month experience in a real parking area showed that this biofilm remained viable without any replenishment of nutrients or bacteria. During accelerated pollution tests at a pilot scale, the structure bioaugmented with pre-coated biofilms was more efficient than a non-inoculated structure to limit hydrocarbon leaching below 50 μg L −1 and to degrade hydrocarbons adsorbed to the gravels. Over the long term, this innovative assembly should maintain the degrading capacity of PPS and ensure an effective treatment of stormwater before its infiltration into the soil. Highlights: A simple method was developed to count cells from biofilms formed on PPS gravels. Rhodococcus erythropolis T902.1 forms resilient biofilms on these PPS gravels. This strain T902.1 maintained in PPS in real conditions of use for more than 1 year. The draining structure can absorb a high amount of diesel before its saturation. During pollution tests, the strain improved the degrading capacity of the structure.